2016
DOI: 10.1093/labmed/lmw017
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Deletion Polymorphisms in Early-Onset Psychotic and Bipolar Disorders: A Case-Control Study

Abstract: The GSTM1-null genotype might be associated with higher risk for early onset severe mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…, ~ 70% in Eurasian populations) [ 6 12 ]. This deletion variant has been associated strongly with susceptibility to bladder cancer [ 13 ], multiple sclerosis [ 14 ] and early onset of severe mental disorders [ 15 ], among other diseases. However, why this deletion has been maintained in human populations remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…, ~ 70% in Eurasian populations) [ 6 12 ]. This deletion variant has been associated strongly with susceptibility to bladder cancer [ 13 ], multiple sclerosis [ 14 ] and early onset of severe mental disorders [ 15 ], among other diseases. However, why this deletion has been maintained in human populations remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] The fact that GSTT1 active genotype is a risk factor for SCZ has been confirmed in many previous studies. [ 35 , 37 , 49 ] In this study, the null genotype proportion of GSTT1 were 45.60% and 50.38% for SCZ patients and healthy individuals, respectively. The results indicated that GSTT1 could be a candidate gene for predisposing to SCZ in Chinese Han population.…”
Section: Discussionmentioning
confidence: 57%
“…The results of our study are supported by Raffa et al, [ 37 ] and they suggested that GSTT1 null genotype might decrease the risk of SCZ in Tunisian. However, Pejovic-Milovancevic et al [ 35 ] and Matsuzawa et al [ 50 ] have demonstrated that GSTT1 polymorphism is not associated with susceptibility to SCZ independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that the GSTM family of genes have critical roles in several cancer types. GSTM1 is highly polymorphic in humans and is associated with multiple cancer types, such as bladder and breast cancer, metabolic disorders and autoimmune diseases, as well as anticancer drugs response and resistance ( 28 ) GSTM1 deletion in humans was indicated to have a key role in bladder ( 29 ) and breast cancer ( 30 , 31 ), multiple sclerosis ( 32 ), severe early-onset mental disorders including schizophrenia-spectrum disorder, bipolar disorder with psychotic symptoms or first-episode psychosis ( 33 ) and acute myeloid leukemia ( 34 ). Csejtei et al ( 35 ) identified that GSTM1 may be a prognostic biomarker in clinical diagnostics as well as a potential therapeutic candidate in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%